Utilising PRA to develop a postgraduate qualification in visual impairment studies - Manis, M.; Ferreira, R.; Sefotho, M.M.; Mampane, R.M. (South African Journal of Higher Education, 2021)
This article reports on the study that focused on the utilisation of a Participatory Reflection and Action (PRA) methodology in order to develop a postgraduate qualification in visual impairment studies. The broader project aims to create ways in which learners with visual impairment can be included in South African schools. In lieu of this, it has therefore come to our attention that teachers of these learners in full service schools (FSS) and special needs schools may require appropriate education and training so as to effectively work with learners with visual impairment. For our exploration, we followed a case study design and utilised PRA approach as the main data generation source in the five provinces that were involved in the study. The sample involved 255 teachers in full service and special needs schools and 50 expert stakeholders in the field of visual impairment. To most teachers, being involved in PRA-based workshops was somewhat new, thus, our study found that teachers have varying views in terms of them (teachers) being part of PRA-based workshops. Although most of them commend the process of these workshops, others feel that there could be an opportunity for improvement.